Association of Daily Step Count with the Prolonged Air Leak in Thoracic Surgery Patients - Kavurmaci, Önder; Ozdil, Ali; Akçam, Tevfik Ilker; Ergonul, Ayse Gul; Turhan, Kutsal; Cakan, Alpaslan; Cagirici, Ufuk (The Thoracic and Cardiovascular Surgeon, 2020)
Background In thoracic surgery clinics, patients are encouraged to walk; however, to our knowledge, there is no data regarding the minimum step count necessary to protect them from complications. In our study, we aim to ascertain the relationship between walking and prolonged air leak (PAL), which is one of the most common complications following thoracic surgery.Methods Patients, who were being followed-up at our clinic between December 2016 and July 2017, were separated into three groups and were investigated prospectively. The groups were established as follows: Group I, included patients with spontaneous pneumothorax; Group II, comprised patients who were applied sublobar lung resection; and Group III, comprised (pneumonectomy excluded) patients who were applied anatomic lung resection. All the patients were supplied with a standard pedometer. The step counts of the patients were recorded prospectively, beginning from the first postoperative day, and an attempt was made to establish the relationship between the patients' daily and mean step counts and the development of PAL.Results PAL developed in 11 (39.29%) of the 28 patients in Group I; in 1 (2.04%) of the 49 patients in Group II and in 22 (36.07%) of the 61 patients in Group III. When receiver operating characteristic (ROC) analysis was applied to the data of Group I, and when the cut-off value for the first-day step count was confirmed to be 2,513 steps, it was revealed that the development of PAL could be determined with a sensitivity of 100% and a specificity of 100%. The analysis of the patients in Group III revealed significant correlations between the first-day and second-day step counts, and the development of PAL (p = 0.017 and 0.007, respectively). The development of PAL decreased as walking was maximized.Conclusion Early and sufficient mobilization decreases the likelihood of postoperative complications. Our study defines concepts, such as post-operative daily step count, target step count, and step count protecting from PAL, and in this regard, we consider it to be a primary study in the literature.
Keywords: pedometer; prolonged air leak; step count; postoperative mobilization